Development Of Mechanisms For Applying Digital Technologies In The Professional Activities Of Future Teachers - Ilhomjon Usmanalievich Nazarov (Euro Asian Journal Publishing, 2024)
The article is devoted to topical problems of preparing future teachers for the use of digital technologies at a high level. There is a need to review existing curricula and subjects to develop future teachers' digital skills in the educational process. A special place in the training of future teachers is occupied by organizations based on the digitalization of methods of teaching school subjects.
Keywords: digital technologies; education; online learning; interactivity